Tannic acid-based epoxy resin and anticorrosive paint
By reacting small molecule tannin with epoxy resin to form a tannin-based epoxy resin and forming a cross-linked network polymer structure with the curing agent, the problem of easy precipitation of small molecule tannin in traditional anticorrosion coatings is solved, and high density and long-term anticorrosion effect is achieved.
Patent Information
- Application Number
- CN202510110529.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-23
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2045-01-23
AI Technical Summary
Small molecule tannin acid in traditional low-surface treatment anticorrosion coatings is easily soluble in water, and the chelates formed gradually precipitate or are washed away in the environment, resulting in the gradual disappearance of adhesion and the long-term anticorrosion effect cannot be achieved.
By chemically reacting small molecule tannin with epoxy resin, a tannin-based epoxy resin is formed, which retains the function of tannin acid and rust to form a chelate, and a thermosetting large-density cross-linked network polymer structure is generated with a curing agent through multiple epoxy structures to fix tannin groups, thereby improving the density and long-term effectiveness of the paint film.
The conversion of rust into dense chelates is achieved, the density and anti-corrosion effect of the paint film is improved, the long-term anti-corrosion performance of low-surface treatment anti-corrosion coatings is ensured, and the adhesion is significantly improved. The neutral salt spray experiment reaches 4500 hours.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coatings, and in particular to a tannic acid-based epoxy resin and an anti-corrosion coating. Background Art
[0002] Metal corrosion is an irreversible spontaneous process. Except for a very small number of precious metals such as gold and platinum, most metals in nature are very likely to undergo chemical or electrochemical reactions under the action of corrosive media in the atmospheric environment, completing the metal corrosion process, including various types of steel structure facilities in the atmospheric environment. Metal corrosion will bring two problems. First, the corrosion of the supporting parts in the steel structure facilities will cause major safety accidents, and second, it will cause huge economic losses. The most effective way to solve metal corrosion is to apply a layer of anti-corrosion coating on its surface to effectively protect the metal and thus increase the service life of the metal. Traditional anti-corrosion coatings require strict surface treatment processes to remove rust on the metal surface before coating, which will not only increase the cost and difficulty of coating, but also generate a lot of dust pollution.
[0003] Low surface treatment anti-corrosion coatings solve the above problems very well. The surface of the metal substrate does not need to be completely treated to the anti-rust standard. It is only necessary to simply remove the floating rust on the surface of the metal substrate. Its main mechanism of action is that certain components in the coating will react with the rust on the surface of the steel, converting it into a stable passivation product, while also improving the adhesion and anti-corrosion effect of the coating. At present, low surface treatment anti-corrosion coatings mainly enhance the adhesion of low surface treatment by forming chelates with metal oxides through small molecule carboxylic acids or phenols such as tannic acid, phosphoric acid, and phytic acid. However, these small molecules can be dissolved in water, and the formed chelates will gradually precipitate or be washed away by rainwater in the environment, resulting in the gradual disappearance of adhesion and the inability to achieve long-term anti-corrosion effects. Summary of the invention
[0004] In view of this, the present invention provides a tannic acid-based epoxy resin and an anti-corrosion coating. After the anti-corrosion coating containing the tannic acid-based epoxy resin provided by the present invention is coated on a metal surface, the surface rust can be converted into a dense chelate, thereby greatly improving the density of the paint film; at the same time, a long-term anti-corrosion effect can be achieved.
[0005] The tannic acid-based epoxy resin provided by the present invention is obtained by reacting tannic acid, a diol compound and an epoxy compound;
[0006] The molar ratio of the tannic acid to the diol compound is 1:10-20;
[0007] The molar ratio of the tannic acid to the epoxy compound is 1:100-200.
[0008] The present invention combines small molecule tannic acid and epoxy resin together through chemical reaction to obtain a novel tannic acid-based epoxy resin. The tannic acid-based epoxy resin retains the function of tannic acid and rust to form a chelate, and can convert rust into a dense chelate, thereby solving the problem of low surface treatment. In addition, multiple epoxy structures in the structure can be cured with a curing agent to generate a thermosetting high-density cross-linked network polymer structure, which greatly improves the density of the paint film and hinders further corrosion of the corrosive medium. Moreover, the network structure firmly fixes the tannic acid structure on the metal substrate, thereby not being affected by the surrounding environment, and ensuring the long-term effectiveness of the low surface treatment anti-corrosion coating.
[0009] In some specific implementations, the tannic acid-based epoxy resin of the present invention is obtained by reacting a reaction product of tannic acid and a diol compound with an epoxy compound. Specifically, tannic acid and the diol compound undergo a first substitution reaction to obtain a tannic acid-based diol. The tannic acid-based diol obtained by the above reaction then undergoes a second substitution reaction with the epoxy compound to obtain the tannic acid-based epoxy resin.
[0010] The tannic acid-based epoxy resin of the present invention may have the following structure, but this structure cannot cover all tannic acid-based epoxy resins provided by the present invention, and the protection scope of the present invention is not limited by this structure;
[0011] .
[0012] The present invention provides a method for preparing the above-mentioned tannic acid-based epoxy resin, comprising:
[0013] Under an inert atmosphere, tannic acid and diol compounds are reacted for the first time under alkaline conditions to obtain tannic acid-based diol.
[0014] The diol compound of the present invention is preferably a diol compound with halogen as the terminal group, and more preferably has the following structure:
[0015] ;
[0016] a and b are independently selected from integers of 1 to 10.
[0017] The epoxy compound of the present invention is preferably an epoxy compound with halogen as the terminal group, and more preferably has the following structure:
[0018] ;
[0019] R is selected from C1~C 10 of alkyl.
[0020] In some specific implementations, the molar ratio of the tannic acid to the diol compound is 1:10-20, preferably 1:10-18, and more preferably 1:10-15. In some specific implementations, the alkaline condition is sodium hydroxide. In some specific implementations, the solvent of the first reaction is water. In some specific implementations, the time of the first reaction is 4-10h, preferably 4-8h, and more preferably 4-6h. In some specific implementations, the time temperature of the first reaction is 80-120°C, preferably 85-115°C, and more preferably 90-110°C.
[0021] After obtaining the tannic acid-based diol, the present invention preferably purifies it to obtain a pure compound. The present invention has no limitation on the purification method, and a purification method well known to those skilled in the art can be selected. The present invention provides a specific purification method: extracting the obtained tannic acid-based diol with an organic solvent and water, retaining the organic phase and washing it with water for 5 to 10 times, and removing water to obtain pure tannic acid-based diol. In some specific implementations, the dehydration is to add anhydrous magnesium sulfate to the solution, let it stand for 40 to 60 hours, and filter to remove the solid.
[0022] The tannic acid-based diol, epoxy compound and catalyst obtained by the above reaction are reacted for a second time under alkaline conditions to obtain the tannic acid-based epoxy resin. In some specific implementations, the second reaction is carried out under an inert atmosphere. In some specific implementations, the alkaline condition is sodium hydroxide. In some specific implementations, the catalyst can be tetrabutylammonium bromide. In some specific implementations, the time of the second reaction is 4 to 10 hours, preferably 4 to 8 hours, and more preferably 4 to 6 hours. In some specific implementations, the temperature of the second reaction is 60 to 100°C, preferably 65 to 95°C, and more preferably 60 to 90°C.
[0023] After obtaining the tannic acid-based epoxy resin, the present invention also preferably purifies it to obtain a pure compound. The purification method is not particularly limited and can be the same as the purification method of the above-mentioned tannic acid-based diol. The present invention will not be repeated here, and those skilled in the art can select the purification method according to their needs.
[0024] Based on the characteristics of the above-mentioned tannic acid-based epoxy resin, the present invention applies it to the field of anti-corrosion coatings and provides an anti-corrosion coating comprising component A and component B.
[0025] The component A comprises the following components in parts by weight:
[0026] The tannic acid-based epoxy resin described in the above technical solution is 13 to 32 parts, preferably 14 to 32 parts, and more preferably 15 to 32 parts; it also includes 18 to 65 parts of glyceryl ether-based epoxy resin, preferably 19 to 65 parts, and more preferably 20 to 65 parts; it also includes 1.5 to 22 parts of polyaniline, preferably 1.5 to 21 parts, and more preferably 1.5 to 20 parts; it also includes 13 to 60 parts of talc, preferably 14 to 60 parts, and more preferably 15 to 60 parts; It also includes 0.35-3.5 parts of dispersant, preferably 0.35-3.4 parts, more preferably 0.35-3.5 parts; it also includes 0.2-3 parts of defoaming agent, preferably 0.2-2.8 parts, more preferably 0.2-2.6 parts; it also includes 1.8-7 parts of anti-settling agent, preferably 1.8-6.7 parts, more preferably 1.8-6.5 parts; it also includes 35-100 parts of diluent, preferably 38-100 parts, more preferably 40-100 parts.
[0027] The component B comprises the following components in parts by weight:
[0028] The present invention further comprises 28 to 50 parts of curing agent, preferably 28 to 47 parts, and more preferably 28 to 45 parts of curing agent; and 18 to 40 parts of diluent, preferably 18 to 37 parts, and more preferably 18 to 35 parts of diluent.
[0029] The anti-corrosion coating provided by the present invention only needs to remove the floating rust on the surface of the metal substrate before coating, and does not need to be completely treated to the anti-rust standard. In addition, the tannic acid-based epoxy resin in the coating is tightly fixed in the mesh structure by the epoxy structure through chemical bonds, thereby solving the problem of precipitation or loss of traditional small molecular tannic acid and improving the long-term effectiveness of the anti-corrosion coating.
[0030] In some specific implementations, the mass ratio of component A to component B is 3-5:1.
[0031] The curing agent can cause the coating surface to harden rapidly, thereby accelerating drying; at the same time, it can significantly improve the hardness of the coating, making the coating more durable and wear-resistant. After the coating is applied, the curing agent will continue to play a role, so that the hardness and toughness of the coating surface are improved, thereby enhancing the protective ability of the coating. In some specific implementations, the curing agent is selected from at least one of polyamide curing agent 650, polyamide curing agent 651, NX-2015, NX-2040, NX-2041 and NX-2045, preferably one or more of polyamide curing agent 650, NX-2015, NX-2040 and NX-2045, and the present invention has no special restrictions on the proportion of each substance.
[0032] The glycerol ether-based epoxy resin can provide anticorrosion protection in the anticorrosive coating, and can also enhance the adhesion, hardness and wear resistance of the coating; due to its water solubility and water dispersibility, the coating does not require an organic solvent during use, which is beneficial to environmental protection and health. In some specific implementations, the glycerol ether-based epoxy resin is selected from one or more of bisphenol A diglycidyl ether, hydrogenated bisphenol A diglycidyl ether, bisphenol F diglycidyl ether and bisphenol S diglycidyl ether, and the present invention has no special restrictions on the proportion of each substance.
[0033] Dispersants can effectively prevent the aggregation of particles of each component of the anti-corrosion coating, thereby ensuring that the coating forms a uniform and dense protective film on the metal surface, which can not only improve the anti-corrosion performance of the coating, but also extend the service life of the metal material. In some specific implementations, the dispersant is selected from at least one of Disperbyk-103, Disperbyk-108, Disperbyk-115, Disperbyk-130, Disperbyk-111, Disperbyk-180, Disperbyk-160, Disperbyk-162, Disperbyk-164 and Disperbyk-182, preferably one or more of Disperbyk-103, Disperbyk-108, Disperbyk-130 and Disperbyk-160, and the present invention has no special restrictions on the proportion of each substance.
[0034] The anti-settling agent can maintain uniform dispersion of pigment particles in the coating, prevent the pigment from settling during storage and construction, maintain uniformity and stability of the coating, and extend the service life of the coating. In some specific implementations, the anti-settling agent is selected from at least one of BYK RHEOBYK-420, BYK RHEOBYK-410, BYK RHEOBYK-405, BYK RHEOBYK-425 and BYK RHEOBYK-430, preferably one or more of BYK RHEOBYK-405 and RHEOBYK-430. The present invention has no particular restrictions on the proportion of each substance.
[0035] Defoaming agents can quickly disperse in the coating system, effectively reduce liquid tension, destroy the stability of foam, achieve rapid defoaming and prevent foam regeneration, significantly improve the construction performance of the coating, make the coating surface smooth and bubble-free, and enhance the anti-corrosion performance. In some specific implementations, the defoaming agent is selected from at least one of BYK-052, BYK-088, BYK-1752, BYK-053, BYK-051, BYK-057, BYK-077, BYK-066N, BYK-392, BYK-333, BYK-141 and BYK-1790, preferably at least one of BYK-052, BYK-088, BYK-1752, BYK-053, BYK-051, BYK-057, BYK-077, BYK-066N and BYK-392, more preferably one or more of BYK-052, BYK-088, BYK-1752, BYK-057 and BYK-392. The present invention has no particular limitation on the proportion of each substance.
[0036] The diluent plays a role in adjusting the viscosity of the anticorrosive coating, which can make the coating easier to construct and spray, while ensuring the smoothness and uniformity of the coating. In some specific implementations, the diluent is selected from one or more of toluene, xylene, propylene glycol methyl ether acetate, propylene glycol methyl ether, ethylene glycol butyl ether, isopropanol, butyl acetate and n-butanol, and the present invention has no special restrictions on the proportion of each substance.
[0037] Polyaniline has excellent chemical stability and electrical activity, and can form a dense protective film in a harsh corrosive environment, effectively isolating the direct contact between the corrosive medium and the substrate, thereby greatly extending the service life of the coated object. In some specific implementations, the polyaniline described in the present invention is phosphate-doped polyaniline, and the present invention has no special restrictions on its source, and it can be purchased or synthesized by itself. For example, it can be prepared by referring to the method provided in the invention patent CN102108241A: intrinsic polyaniline, phosphate and water are mixed in a molar ratio of 1: (0.1~0.5): (40~5), and the phosphate-doped polyaniline is obtained after reacting for 2~6 hours.
[0038] On this basis, the present invention also provides a method for preparing the above-mentioned anticorrosive coating, which specifically comprises:
[0039] The tannic acid-based epoxy resin, glycerol ether-based epoxy resin, polyaniline, precipitated barium sulfate, talcum powder, dispersant, defoamer and diluent are fully mixed and dispersed uniformly, and then mixed with an anti-settling agent to obtain component A;
[0040] Mix the curing agent and the diluent to obtain component B;
[0041] Component A and component B are mixed evenly to obtain the anti-corrosion coating.
[0042] In some specific implementations, the dispersing operation is specifically as follows: adding each component to a high-speed disperser, dispersing at a speed of 1000-1500 rpm for 15-45 minutes, then adding to a sand mill, sand milling for 1-3 hours, filtering with a 75-85 mesh filter, and retaining the filtrate.
[0043] The present invention combines small molecule tannic acid with epoxy resin to obtain a tannic acid-based epoxy resin, which retains the function of tannic acid and rust to form a chelate, and can convert rust into a dense chelate; at the same time, the tannic acid-based epoxy resin can generate a high-density cross-linked structure coating with a curing agent, and the tannic acid group is tightly fixed in the above-mentioned cross-linked network structure by the epoxy structure, thereby solving the problem of precipitation or loss of traditional small molecule tannic acid and improving the long-term anti-corrosion performance of the coating. Experimental results show that the tannic acid-based epoxy resin provided by the present invention has an adhesion to the substrate of more than 13MPa after being used in the anti-corrosion coating, and the neutral salt spray test reaches 4500 hours, which has excellent anti-corrosion effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 The photos and adhesion of the anti-corrosion coating of Example 2 before the salt spray test;
[0045] Figure 2 The photos and adhesion of the anti-corrosion coating after salt spray test of Example 3;
[0046] Figure 3 The photos and adhesion of the anti-corrosion coating of comparative example 4 before the salt spray test;
[0047] Figure 4 These are photos and adhesion of the anti-corrosion coating of comparative example 4 after salt spray test. DETAILED DESCRIPTION
[0048] It should be understood that the expression "one or more of..." includes each of the items recited after the expression individually and in various different combinations of two or more of the recited items, unless otherwise understood from the context and usage. The expression "and / or" in combination with three or more recited items should be understood to have the same meaning, unless otherwise understood from the context.
[0049] The use of the terms "comprising", "having" or "containing", including their grammatical synonyms, should generally be understood as open and non-restrictive, for example not excluding other unrecited elements or steps, unless otherwise specifically stated or otherwise understood from the context.
[0050] It should be understood that the order of steps or the order in which certain actions are performed is not important as long as the present invention remains operable. In addition, two or more steps or actions may be performed simultaneously.
[0051] The use of any and all examples or exemplary language, such as "for example" or "including", herein is intended only to better illustrate the invention and does not limit the scope of the invention unless otherwise claimed. No language in this specification should be construed as indicating that any non-claimed element is essential to the practice of the invention.
[0052] In addition, the numerical ranges and parameters used to define the present invention are approximate values, and the relevant values in the specific embodiments have been presented as accurately as possible. However, any numerical value inherently inevitably contains standard deviations due to individual test methods. Therefore, unless otherwise expressly stated, it should be understood that all ranges, quantities, values and percentages used in this disclosure are modified by "about". Here, "about" generally means that the actual value is within plus or minus 10%, 5%, 1% or 0.5% of a specific value or range.
[0053] The present invention provides a tannic acid-based epoxy resin obtained by reacting tannic acid, a diol compound and an epoxy compound;
[0054] The molar ratio of the tannic acid to the diol compound is 1:10-20;
[0055] The molar ratio of the tannic acid to the epoxy compound is 1:100-200.
[0056] The present invention combines small molecule tannic acid and epoxy resin together through chemical reaction to obtain a novel tannic acid-based epoxy resin. The tannic acid-based epoxy resin retains the function of tannic acid and rust to form a chelate, and can convert rust into a dense chelate, thereby solving the problem of low surface treatment. In addition, multiple epoxy structures in the structure can be cured with a curing agent to generate a thermosetting high-density cross-linked network polymer structure, which greatly improves the density of the paint film and hinders further corrosion of the corrosive medium. Moreover, the network structure firmly fixes the tannic acid structure on the metal substrate, thereby not being affected by the surrounding environment, and ensuring the long-term effectiveness of the low surface treatment anti-corrosion coating.
[0057] The present invention is further described below in conjunction with the following examples. The protection scope of the present invention is not limited by the following examples.
[0058] Example 1
[0059] (1) Under nitrogen protection, 24 g of sodium hydroxide and 75.1 g of tannic acid were dissolved in 176 g of deionized water and stirred at 100 °C for 1 h to form a clear liquid. Then 66.3 g of 3-chloro-1,2-propanediol was added and reacted for 4 h. After the reaction, 450 ml of toluene was added to extract the reaction liquid, and the organic phase was retained and washed with 200 ml of deionized water. The washing process was repeated 8 times, and anhydrous magnesium sulfate was added to the organic phase. The mixture was left at room temperature for 48 hours, filtered, and the filtrate was collected.
[0060] (2) Under nitrogen protection, add 577.3 g of epichlorohydrin to the filtrate obtained in the first step, stir at 80°C for 30 min, then add tetrabutylammonium bromide, 38 g of sodium hydroxide and 180 g of deionized water, and continue to react for 5 h. After the reaction is completed, add 200 g of xylene, separate the water phase, retain the organic phase, add 150 g of deionized water to the organic phase, stir at room temperature for 20 min, separate the water phase, retain the organic phase, repeat this process 8 times, add anhydrous magnesium sulfate to the obtained organic phase, filter, obtain a filtrate, remove the solvent from the filtrate under negative pressure, and obtain a tannic acid-based epoxy resin.
[0061] Example 2
[0062] (1) 15 g of tannic acid-based epoxy resin (prepared in Example 1), 20 g of bisphenol A diglycidyl ether, 1.5 g of polyaniline, 25 g of precipitated barium sulfate, 15 g of talc, 0.35 g of Disperbyk-103, 0.2 g of BYK-052 and 50 g of xylene were mixed and added to a high-speed disperser, dispersed at a speed of 1000 rpm for 30 min, then added to a sand mill, sand milled for 1.5 hours, filtered with an 80-mesh filter, and the filtrate was added to the disperser, 1.8 g of BYK RHEOBYK-420 was added, and stirred for 15 min to obtain component A;
[0063] (2) Add 45 g of polyamide curing agent 650 and 10 g of xylene into a mixing tank and stir for 15 min to obtain component B;
[0064] (3) Component A and component B are mixed in a weight ratio of 3:1 to obtain a low surface treatment anti-corrosion coating.
[0065] Example 3
[0066] (1) 32 g of tannic acid-based epoxy resin (prepared in Example 1), 65 g of hydrogenated bisphenol A diglycidyl ether, 15 g of polyaniline, 55 g of precipitated barium sulfate, 60 g of talc, 3.1 g of Disperbyk-108, 2.6 g of BYK-088 and 85 g of toluene were mixed and added to a high-speed disperser, dispersed at a speed of 1500 rpm for 30 min, then added to a sand mill, sand milled for 1.5 hours, filtered with an 80-mesh filter, and the filtrate was added to the disperser, 6.5 g of BYK RHEOBYK-410 was added, and stirred for 15 min to obtain component A;
[0067] (2) Add 42 g of curing agent NX-2015 and 26 g of toluene diluent into a mixing tank and stir for 15 min to obtain component B;
[0068] (3) Component A and component B are mixed in a weight ratio of 5:1 to obtain a low surface treatment anti-corrosion coating.
[0069] Example 4
[0070] (1) 26 g of tannic acid-based epoxy resin (prepared in Example 1), 45 g of bisphenol F diglycidyl ether, 3.5 g of polyaniline, 32 g of precipitated barium sulfate, 24 g of talc, 1.2 g of Disperbyk-130, 0.8 g of BYK-1752, 40 g of xylene and 10 g of isopropanol were mixed and added to a high-speed disperser, dispersed at a speed of 1200 rpm for 30 min, then added to a sand mill, sand milled for 1.5 hours, filtered with a 80-mesh filter, and the filtrate was added to the disperser, 3.5 g of BYK RHEOBYK-405 was added, and stirred for 15 min to obtain component A;
[0071] (2) Add 35 g of curing agent NX-2040 and 26 g of butyl acetate into a mixing tank and stir for 15 min to obtain component B;
[0072] (3) Component A and component B are mixed in a weight ratio of 4:1 to obtain a low surface treatment anti-corrosion coating.
[0073] Example 5
[0074] (1) 24 g of tannic acid-based epoxy resin (prepared in Example 1), 49 g of bisphenol S diglycidyl ether, 3.7 g of polyaniline, 36 g of precipitated barium sulfate, 43 g of talc, 1.35 g of Disperbyk-180, 1.4 g of BYK-057 and 48 g of xylene were mixed and added to a high-speed disperser, dispersed at a speed of 1200 rpm for 30 min, then added to a sand mill, sand milled for 1.5 hours, filtered with a 80-mesh filter, and the filtrate was added to the disperser, 5.1 g of BYK RHEOBYK-425 was added, and stirred for 15 min to obtain component A;
[0075] (2) Add 32 g of NX-2045 and 28 g of xylene into a mixing tank and stir for 15 min to obtain component B;
[0076] (3) Component A and component B are mixed in a weight ratio of 3.5:1 to obtain a low surface treatment anti-corrosion coating.
[0077] Example 6
[0078] (1) 30.5 g of tannic acid-based epoxy resin (prepared in Example 1), 27.3 g of bisphenol F diglycidyl ether, 6.8 g of polyaniline, 32.8 g of precipitated barium sulfate, 45.8 g of talc, 2.3 g of Disperbyk-160, 1.35 g of BYK-392, 41 g of n-butanol and 18 g of xylene were mixed and added to a high-speed disperser, dispersed at a speed of 1000 rpm for 30 min, then added to a sand mill, sand milled for 1.5 hours, filtered with a 80-mesh filter, and the filtrate was added to the disperser, 4.7 g of BYK RHEOBYK-420 was added, and stirred for 15 min to obtain component A;
[0079] (2) Add 34.6 g of NX-2015 and 27 g of xylene into a mixing tank and stir for 15 min to obtain component B;
[0080] (3) Component A and component B are mixed in a weight ratio of 4.5:1 to obtain a low surface treatment anti-corrosion coating.
[0081] Comparative Example 1
[0082] Compared with Example 2, the difference is that in step (1), 15 g of phytic acid is used instead of 15 g of tannic acid-based epoxy resin, and the other contents are the same.
[0083] Comparative Example 2
[0084] Compared with Example 2, the difference is that in step (1), 15 g of tannic acid is used instead of 15 g of tannic acid-based epoxy resin, and the rest is the same.
[0085] Comparative Example 3
[0086] Compared with Example 2, the difference is that polyaniline is not included in step (1), and the others are the same.
[0087] Comparative Example 4
[0088] Compared with Example 2, the difference is that the tannic acid-based epoxy resin is not included in step (1), and the other steps are the same.
[0089] Test Example 1
[0090] The anticorrosive coatings of Examples 2 to 6 and Comparative Examples 1 to 5 were brush-coated on steel plates with surfaces treated to St2 or Sa2 levels, and then dried at room temperature for 7 days before performance testing.
[0091] Coating adhesion test: Use Positest AT-M20mm puller to test according to GB / T5210 pull-off method. Test at least 3 points on each sample, and take the average value of the 3 points as the adhesion data.
[0092] Coating impact resistance test: Tested in accordance with GB / T 1732 standard.
[0093] Coating bending resistance test: Tested in accordance with GB / T 6742 standard.
[0094] Neutral salt spray test of coating: Use F-90 salt spray corrosion tester (Qingdao Yitai Instrument Co., Ltd.) to test according to national standard GB10125-2012: the concentration of sodium chloride solution in the salt spray chamber is 50g / L, the pH value is 6.5~7.2, and the test temperature is fixed at (35±2)℃. Salt spray resistance performance requirements: no blistering, no cracking, no shedding, no rust.
[0095] Figure 1 Shown are photos of the coating formed by the anti-corrosion coating prepared in Example 2 and the adhesion test results thereof; Figure 2 Shown are photos and adhesion test results of the anti-corrosion coating prepared in Example 3 after 4500 hours of salt spray test; Figure 3 Shown are photos of the coating formed by the anti-corrosion coating prepared in Comparative Example 4 and the adhesion test results; Figure 4 The photo and adhesion test results of the anticorrosive coating prepared in comparative example 4 after 200 hours of salt spray test are shown. It can be seen intuitively that the coatings formed by the anticorrosive coatings prepared in examples 2 and 3 are better than those in comparative example 4 in terms of integrity and adhesion.
[0096] The anti-corrosion coating performance test data of Examples 2 to 6 and Comparative Examples 1 to 4 are summarized in Table 1.
[0097] Table 1. Anticorrosion coating performance test data of Examples 2 to 6 and Comparative Examples 1 to 4
[0098]
[0099] As can be seen from the data in Table 1, Comparative Examples 1 and 2 used small molecular tannic acid and phytic acid as substances that react with rust, and it was found that no long-term anticorrosion performance could be obtained. However, their anticorrosion performance was better than that without polyaniline, because polyaniline itself can provide excellent long-term anticorrosion performance. Comparative Example 3 did not have a polyaniline component, so its long-term anticorrosion performance was greatly affected. The results of Comparative Example 4 showed that it did not have a low surface treatment effect, the adhesion was very low, and the loose coating caused the corrosive medium to easily pass through the coating, resulting in the inability to show the anticorrosion performance of polyaniline, and the anticorrosion performance was very poor, because there was no component that could react with rust.
[0100] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A tannic acid-based epoxy resin, characterized in that It is obtained by the reaction of tannic acid, diol compounds and epoxy compounds; The molar ratio of the tannic acid to the diol compound is 1:10-20; The molar ratio of the tannic acid to the epoxy compound is 1:100-200.
2. The tannic acid-based epoxy resin according to claim 1, characterized in that It is obtained by reacting the reaction product of tannic acid and diol compounds with epoxy compounds; The diol compound is a diol compound with halogen as the terminal group; The epoxy compound is an epoxy compound with halogen as the terminal group.
3. The tannic acid-based epoxy resin according to claim 2, characterized in that The diol compound has the following structure: ; a and b are independently selected from integers of 1 to 10.
4. The tannic acid-based epoxy resin according to claim 2, characterized in that The epoxy compound has the following structure: ; R is selected from C1~C 10 of alkyl.
5. An anti-corrosion coating, characterized in that: Comprising component A and component B; The component A comprises the following components in parts by weight: 13-32 parts of the tannic acid-based epoxy resin according to any one of claims 1 to 4, 18-65 parts of a glyceryl ether-based epoxy resin, 1.5-22 parts of polyaniline, 13-60 parts of talc, 0.35-3.5 parts of a dispersant, 0.2-3 parts of a defoamer, 1.8-7 parts of an anti-settling agent, and 35-100 parts of a diluent; The component B comprises the following components in parts by weight: 28 to 50 parts of a curing agent and 18 to 40 parts of a diluent.
6. The anticorrosive coating according to claim 5, characterized in that: The mass ratio of component A to component B is 3-5:
1.
7. The anticorrosive coating according to claim 5, characterized in that: The curing agent is selected from at least one of polyamide curing agent 650, polyamide curing agent 651, NX-2015, NX-2040, NX-2041 and NX-2045.
8. The anticorrosive coating according to claim 5, characterized in that: The glyceryl ether-based epoxy resin is selected from at least one of bisphenol A diglycidyl ether, hydrogenated bisphenol A diglycidyl ether, bisphenol F diglycidyl ether and bisphenol S diglycidyl ether.
9. The anticorrosive coating according to claim 5, characterized in that: The dispersant is selected from at least one of Disperbyk-103, Disperbyk-108, Disperbyk-115, Disperbyk-130, Disperbyk-111, Disperbyk-180, Disperbyk-160, Disperbyk-162, Disperbyk-164 and Disperbyk-182.
10. The anticorrosive coating according to claim 5, characterized in that: The anti-settling agent is selected from at least one of BYK RHEOBYK-420, BYK RHEOBYK-410, BYK RHEOBYK-405, BYK RHEOBYK-425 and BYK RHEOBYK-430.
Citation Information
Patent Citations
Phosphate doped polyaniline anticorrosive paint and preparation method thereof
CN102108241A
Preparation method of tannic acid modified urushiol glycidyl ether water-based paint
CN107793926A
Polyvalent hydroxy resin, epoxy resin, method for producing them, epoxy resin composition and its cured product
JP2012057079A
Epoxy composition comprising a bio-based epoxy compound
US20230312911A1
Esterified epoxy resin, method for producing same, and curable composition comprising same
WO2013172450A1